Chaetoceros muelleri sulfated polysaccharides: chain conformation, physical characteristics, and morphology - Valeria Miranda-Arizmendi; Jorge Marquez-Escalante; Agustin Rascon-Chu; Karla Martínez-Robinson; Francisco Brown-Bojorquez; Elizabeth Carvajal-Millan (AIMS Biophysics)
Increasing interest in biopolymers moves their knowledge frontiers. One area undergoing this development is polysaccharides. The practical and theoretical significance of studying polysaccharides lies in the numerous essential functions these macromolecules fulfill in living organisms, and the important industrial and technological purposes they serve. Polysaccharides are thought to be abundant in marine microalgae; nevertheless, little is known about their sulfated polysaccharides. We studied Chaetoceros muelleri sulfated polysaccharide (CMSP) chain conformation, physical characteristics, and morphology. The CMSP spectrum generated from Fourier-transform infrared analysis displayed distinctive bands for these macromolecules. S=O and C–O–S signals were detected at 1225 and 820 cm−1, respectively, confirming the presence of sulfate in the molecules. The biopolymer registered weight-average molar mass, intrinsic viscosity ([η]), radius of gyration (RG), hydrodynamic radius (Rh), and sulfate degree of substitution of 1933 kDa, 577 mL/g, 62 nm, 44 nm, and 0.5 (sulfates per disaccharide repeat unit), respectively. The exponent α and the coefficient K in the Mark-Houwink-Sakurada (MHS) equation were 0.76 and 9.76 x 10−3 mL/g, respectively. These values suggest a flexible and compact random coil structure in CMSP. The sample's zeta potential (ζ), conductivity, and diffusion coefficient (D) were −26.43 mV, −2.07 µm cm/s V, 1.25 mS/cm, and 1.8 × 10−8 cm2/s, correspondingly. The negative charge in the molecules is related to the sulfate groups contained. The CMSP surface was coarse and craggy, according to scanning electron microscopy (SEM). The information generated in this present study contributes to elucidating characteristics as fundamental knowledge to understand the macromolecule functionality.